Inovasi Kurikulum dalam Upaya Meningkatkan Mutu Pendidikan (Studi Multi Kasus di MTsN Watulimo) - Muslimin, Nur (Institut Agama Islam Negeri (IAIN) Tulungagung, 2016)
In the planning aspect of curriculum innovation to improve the quality of education well planned. An overview of the current condition of madrasah, the priority of innovation undertaken, planned in a coordinated framework. This means that the plan has previously been communicated by the headmaster with the various parties involved with the madrasah, such as teachers, staff, school committee and the parents or guardians of the students. In general planning of curriculum innovation in the form of additional hours of face to face particular subject, additional tutoring program, local content and skills Javanese fashion, language tutoring program, extracurricular programs, the conditioning program and a computer program; In the aspect of implementation, also performed well. This means before the plan implemented curriculum innovation, the need for certainty is also done by the headmaster and the people involved in the management. The school principal who had previously held agreements with teachers, staff, school committee and parents of students. So during this implementation can be said not encountered significant obstacles; and the aspect of evaluation headmaster do so through various meetings and in meetings. For a meeting with the deputy head of the Madrasah done once a month, while the teacher is done two times in one semester. As for the evaluation of the Madrasah Committee as well as with the parents at the end of the semester.